2019
DOI: 10.1002/14651858.cd000154.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Combined hormonal contraceptives for heavy menstrual bleeding

Abstract: Background Menorrhagia or heavy menstrual bleeding (HMB) is an excessive blood loss that impairs a woman's quality of life, either physical, emotional, social or material. It is benign and not associated with pregnancy or any other gynaecological or systemic disease. Medical treatments used to reduce excessive menstrual blood loss (MBL) include prostaglandin synthetase inhibitors, antifibrinolytics, oral contraceptive pills, and other hormones. The combined oral contraceptive pill (COCP) is claimed to have a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 47 publications
0
55
0
4
Order By: Relevance
“…In the present review, one included study reported that the LNG‐IUS was more effective than COC in terms of bleeding and pain among patients with adenomyosis. Similarly, a recent Cochrane review on eight trials reported that LNG‐IUS was associated with a greater reduction in bleeding compared with COC in women with heavy menstrual bleeding . As mentioned before, hysterectomy is the only definitive therapy for adenomyotic lesions.…”
Section: Discussionmentioning
confidence: 82%
“…In the present review, one included study reported that the LNG‐IUS was more effective than COC in terms of bleeding and pain among patients with adenomyosis. Similarly, a recent Cochrane review on eight trials reported that LNG‐IUS was associated with a greater reduction in bleeding compared with COC in women with heavy menstrual bleeding . As mentioned before, hysterectomy is the only definitive therapy for adenomyotic lesions.…”
Section: Discussionmentioning
confidence: 82%
“…Regarding ovulation suppression, COC can achieve significant results. However, the effect of reducing menstruation is unsatisfactory: the treatment success rate is from 36.8% (13) to 68% (14). In our case, the patient's repeated history of hypermenorrhea with hospitalization discouraged her parents from assuming such a high risk of failure, whether it was for economic or spiritual considerations, they refused to try COC treatment and planned to have her uterus removed to completely cure her AUB-C.…”
Section: Discussionmentioning
confidence: 75%
“…On the one hand, the estrogen component in COC prevents follicle-stimulating hormone secretion and the development of a dominant follicle, and the progestogen prevents the luteinizing hormone surge and ovulation, which will avoid the rupture of the follicle and corpus luteum from the root cause. On the other hand, the progestogen creates an atrophic endometrial lining, that reduces overall blood loss at the time of menstruation (14). Regarding ovulation suppression, COC can achieve significant results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy Menstrual Bleeding (HMB) Early anecdotal evidence, but only few randomized trials (Lethaby et al 2019), strongly support the impact of COC on reducing menstrual bleeding volume and preventing the risk of secondary anemia. COC at different dosages are used in the management of dysfunctional heavy menstrual bleeding from menarche but also in adenomyosis, leiomyomas, and hemostasis disorders.…”
Section: Benefits Of Hormonal Contraceptive Usementioning
confidence: 99%